Navigating the Tides of Change: Analyzing Indonesia's Employment and Unemployment Dynamics from 2011 to 2023 - Nico Pranata Mulya (Institute of Advanced Knowledge and Science, 2024)
Indonesia's labor market has experienced significant shifts and challenges between 2011 and 2023, with the country navigating through global economic crises, technological advancements, and the unprecedented COVID-19 pandemic. This study aims to conduct a comprehensive analysis of the employment and unemployment dynamics in Indonesia during this period, utilizing data from BPS statistical records. The research employs descriptive statistical analysis, time trend analysis, correlation analysis, and comparative analysis to examine the main trends in the workforce, identify key factors influencing labor dynamics, and assess the impact of various economic and social factors on the unemployment rate and working population. The findings reveal that Indonesia's employment rate has shown an overall upward trend, despite fluctuations, while the unemployment rate has generally declined, with the exception of the sharp increase during the COVID-19 pandemic. The study highlights the importance of economic growth, institutional policies, structural transformation, and educational attainment in shaping Indonesia's labor market. The results contribute to a deeper understanding of the complex employment dynamics in Indonesia and provide valuable insights for policymakers in developing agile and responsive strategies to foster inclusive growth, create better jobs, and enhance labor market resilience. The study concludes that comprehensive and adaptable policies are crucial in addressing the evolving challenges and opportunities in Indonesia's labor market, ensuring a sustainable and inclusive